Dark satisfaction in Guanajuato's Mummies Museum visitors - Juan Gabriel Brida; Erika Lourdes González Rosas; María Nela Seijas Giménez (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: The purpose of this study is to explain the determinants of the degree of visit satisfaction to the Guanajuato Mummies Museum. The study contributes to the literature related to perceptions and attitudes of museum visitors, by identifying what factors explain the satisfaction with the visit; as to the best of our knowledge, no similar investigation has been carried out yet. Methods: A survey was used to collect the data (n=392) from national and foreign visitors of the said museum, containing sociodemographic variables, opinions and feelings of the visitors and information about the visit. Data analysis was conducted with an ordered Logit model. Results: Findings indicate that opinions about the activity of the museum, the guided tour and the rest area are the most significant determinants of visitors' satisfaction, while the library and facilities for the disabled are moderately important. Feelings of enjoyment, tiredness or boredom marginally affect visitors' satisfaction. Implications: Knowledge of the satisfaction factors can guide marketing strategies and direct the training of personnel as recommended by ICOM (International Council of Museums) to continue contributing to the improvement of services offered, increasing the levels of satisfaction, and leading to repeat visits.
Keywords: L83; N36; 330; Dark tourism; logit model; Visitors' satisfaction